Significance of androgen receptor and its potential for anti-androgen/androgen receptor-antagonist therapy in ovarian cancers - Teresa H. Kim; Sanaz Memarzadeh; Saba Vahdatshariatpanahi; Nora Ostrzega; Yuna Kang; Neda A. Moatamed (PLoS ONE, 2025)
Introduction Androgen promotes tumorigenesis in some cancers; however, androgen receptor (AR) is not commonly examined in ovarian cancers (OCs). In this study, we evaluated AR expression among different types of OCs and compared the results to estrogen and progesterone receptors (ER & PR). Materials and methods AR, ER, and PR expressions were assessed in 62 cases which were categorized into: low-grade serous carcinoma (LGSCA), high-grade serous carcinoma (HGSCA), clear cell carcinoma (CCCA), ovarian endometrioid carcinoma (OECA), and granulosa cell tumor (GCT). The hormone receptors were compared and evaluated in relation to p53 and body mass index (BMI) using Fisher’s Exact test. Results In a majority of cases, expression of AR was concordant with ER and/or PR. Positivity for all three receptors was observed in 100% of OECAs. AR expression was seen in 92% of HGSCAs as opposed to 88% and 44% for ER and PR. LGSCAs had expressed AR and ER (100%), and PR (70%). In GCTs, positivity rates were 92%, 62%, and 92% for AR, ER, and PR. In rare cases of HGSCA and CCCA, AR was positive despite negative ER and PR. Conclusion AR is expressed in a high percentage of OCs, even more frequently than ER and PR in certain high-grade histological types. Overall, our findings are similar to the results of recent studies of AR expression in endometrial cancers. These findings support an important possible role for AR in OCs as a potential marker to serve as a therapeutic target in these malignancies.